Prevalence of hypertension and its association with obesity in children of selected schools of Bengaluru city - Devadas, Sahana; Arun, P; Premalatha, R (Indian Journal of Child Health, 2017)
Background: Childhood hypertension and its association with obesity are becoming important issues worldwide. The prevalence of hypertension and obesity are increasing in both developed and developing countries. Objectives: To determine the prevalence of hypertension among school-aged children in Bengaluru and to determine whether or not obesity is associated with hypertension. Materials and Methods: Six schools were selected at random from an area in Bengaluru. A total of 3,000 students studying from 1 to 10 grades were included in the study. The students were visited at school, and their weights, heights, and blood pressures (BP) were measured. The World Health Organization’s references were used to determine the prevalence of overweight, obesity, and hypertension. Results: The prevalence of hypertension and obesity were 3.5% (n=106) and 8.2% (n=247), respectively. Sex and obesity were found to be positively associated with hypertension. Conclusion: The prevalence of obesity and hypertension are high among school children of 6-15 years of age in Bengaluru. Obesity is positively associated with hypertension. BP measurements should be part of routine school health examination, especially in obese children.